Biophysical properties and supramolecular structure of self-assembled liposome/ε-peptide/DNA nanoparticles : correlation with gene delivery - Yan, Jiang (2013)
Using solid-phase synthesis, lysine can be oligomerized by a reaction of the peptide carboxylate with the ε-amino group to produce nontoxic, biodegradable cationic peptides, ε-oligo(l-lysines). Here α-substituted derivatives of such ε-oligo(l-lysines) containing arginine and histidine in the side chain were tested as vectors for in vitro gene delivery. Combination of ε-oligolysines with the cationic lipid DOTAP and plasmid DNA resulted in transfection efficiency exceeding that of DOTAP alone, without significant increase in cytotoxicity. Synchrotron small-angle X-ray scattering studies revealed self-assembly of the DOTAP, ε-oligolysines, and DNA to ordered lamellar complexes. High transfection efficiency of the nanoparticles correlates with increase in zeta potential above +20 mV and requires particle size to be below 500 nm. The synergistic effect of branched ε-oligolysines and DOTAP in gene delivery can be explained by the increase in surface charge and by the supramolecular structure of the DOTAP/ε-oligolysine/DNA nanoparticles.